Impact of Second Wave of Corona Virus Disease-2019 on Utilisation Pattern of Dental Services in a Dental Teaching Hospital - Dahal, Sirjana; Niroula, Deepa; Yadav, Rajiv; Poudel, Prakash (Journal of Nepalese Society of Periodontology and Oral Implantology, 2021)
Introduction: COVID-19 brought fear in utilisation of dental services and a critical challenge to dental institutions on how to respond to the dental emergency conditions. Objective: To assess the impact of second wave of COVID-19 on utilisation patterns of dental services in a dental hospital of Kathmandu. Methods: Analytical cross-sectional study was conducted among all individuals visiting outpatient department of a dental teaching hospital, Kathmandu during lockdown and were assessed for chief complaint, examined orally and referred to specialty departments according to treatment need. It was then compared with referral done in pre-lockdown period. Data were analysed in SPSS. Frequency, percentage, mean and standard deviation were calculated depending upon the nature of data. Chi-square test was done for determining association between different variables. Results: During lockdown, majority (67, (28.5%) complained of dental pain, trauma or had hopeless tooth requiring referral to Department of Oral and Maxillofacial Surgery followed by dental problems of endodontic concern (50, 21.3%) with need of referral to Department of Conservative Dentistry and Endodontics. However, during the pre-lockdown period, majority (377, 33.1%) were referred to Department of Conservative Dentistry and Endodontics followed by referral to Department of Oral and Maxillofacial Surgery (275, 24.1%). The proportional difference in referral between two periods were statistically significant (P <0.001). Conclusion: The study concluded that the second wave of COVID-19 lockdown had impact on utilisation of dental services. Safety protocols including proper infection control measures need to be implemented to reduce the risk of transmission and provide quality oral health services.